Pozajęzykowe komponenty jednostki dydaktycznej - Szafernakier-Świrko, Anna (Studia Rossica Posnaniensia, 2017)
In the article the author presents the non-linguistic elements of a didactic unit and demonstrates their important role in designing effective language classes. According to the author, non-linguistic elements include: the teacher’s personality, paralinguistic messages conveyed by the teacher and non-linguistic tools used by the teacher (games, realia and topic related slides).